Paleoecological and Archaeological Investigation of the ROMO 9 Ice Patch, Rocky Mountain National Park, Colorado, USA - LaBelle, Jason M.; Meyer, Kelton A (Journal of Glacial Archaeology, 2021)
Rocky Mountain National Park contains a dense record of prehistoric Native American archaeological locales and biological resources, but questions remain about the past use of the Park’s ice patches by ancient humans and animals. Our survey of 30 locations in the Park revealed that the majority of ice patches are small in size and contain limited evidence of past visitation by mobile peoples, but moderate use by game. In this paper, we present new radiocarbon dates for materials documented in the recently melted forefield of the ROMO 9 ice patch, a mid-sized ice body located in alpine tundra along the Continental Divide. Dated materials include timber-sized pine trees, keratin and bone collagen from large game (bighorn sheep, elk), and a possible wooden artifact made from Mountain mahogany. Results suggest most finds date to several periods of known neoglaciation, during the mid-Holocene (c. 4150 cal BP) and the Little Ice Age (c. 115 cal BP). Our results corroborate past findings on mid-Holocene timberline in the Colorado Front Range, as well as the paucity of archaeological evidence from small ice patches in Colorado.